Angela's ashes : a memoir of a chilhood - McCourt, Frank (London : Flamingo, 1997)
A memoir of growing up in New York in the 1930s and in Ireland in the 1940s. McCourt tells of extreme hardship and suffering, in Brooklyn tenements and Limerick slums - too many children, too little money, his mother barely coping as his father's drinking bouts brought the family close to disaster.
Keywords: McCourt, Frank; Irish Americans -- Biography; Irish Americans -- Ireland -- Limerick (Limerick) -- Biography; Limerick (Limerick, Ireland)